Pengaruh Financial Literacy, Financial Inclusion dan Financial Attitude Terhadap Pengelolaan Keuangan oleh Pelaku UMKM (Studi Kasus pada Pelaku UMKM Kecamatan Lowokwaru, Kota Malang) - Yunita, Rika; Nurhajati, Nurhajati; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine the influence of Financial Literacy, Financial Inclusion, and Financial Attitude on Financial Management by Micro, Small, and Medium Enterprises (MSMEs) practitioners. The study employs a quantitative research approach, utilizing a questionnairebased data collection method. The sample for this research comprises 100 MSME practitioners located in the Lowokwaru Subdistrict, Malang City, and data processing is conducted using the SPSS program. The research has undergone validity and reliability tests. The data analysis methods include classical assumption tests, multiple linear regression tests, statistical tests, and determination coefficient tests. The results of this study indicate that (1) Financial Management by MSME practitioners in the Lowokwaru Sub-district, Malang City, has a positive and significant influence on Financial Literacy, Financial Inclusion, and Financial Attitude. (2) Financial Literacy has a positive influence on Financial Management by MSME practitioners in the Lowokwaru Subdistrict, Malang City. (3) Financial Inclusion has a positive influence on Financial Management by MSME practitioners in the Lowokwaru Sub-district, Malang City. (4) Financial Attitude has a positive influence on Financial Management by MSME practitioners in the Lowokwaru Subdistrict, Malang City.